Downregulation of AdipoR1 in the hippocampus impairs synaptic function and structure and causes depression-like behavior - Peilin Zhu; Yanmin Luo; Yue Li; Jing Tang; Li Liu; Yuhui Deng; Jing Li; Lin Jiang; Wenyu Yang; Qian Xiao; Shun Wang; Yuning Zhou; et al. (Translational Psychiatry)
Abstract Previous studies have indicated that impaired synaptic plasticity is a main pathological alteration in depression. However, the mechanism underlying this pathological change has not been clarified. Adiponectin, an adipokine, crosses the blood‒brain barrier to function in specific brain regions. Previous studies have suggested that the downregulation of adiponectin signaling is involved in the occurrence of depression. The adiponectin receptors (AdipoRs) AdipoR1 and AdipoR2, which serve as the main receptors for adiponectin in the central nervous system, mediate the downstream biological effects of this compound, which has been reported to have positive effects on synaptic plasticity. However, it is not clear whether alterations in adiponectin/AdipoR signaling are associated with impaired synaptic plasticity in depression. Therefore, the aim of this study was to investigate whether changes in the adiponectin/AdipoR pathway in the hippocampus during depression are involved in the regulation of synaptic plasticity damage. We detected reduced plasma concentrations of adiponectin and lower expression levels of AdipoR1 but not AdipoR2 in the hippocampi of mice exposed to chronic unpredictable stress. An adeno-associated virus was subsequently used to knockdown hippocampal AdipoR1 to further verify the effects of decreased expression levels of this receptor on depressive-like behaviors and hippocampal synaptic plasticity. We found that the mice in which hippocampal AdipoR1 was knocked down presented with anhedonia and passive stress-coping behaviors as well as a decreased number of dendritic spines and density of excitatory and inhibitory synapses. Our results suggest that the downregulation of AdipoR1 expression might be an important factor that causes impaired synaptic plasticity in depression. These results may provide new insights into the pathogenesis of depression and new therapeutic targets for treating this disease.